Moral Foundations of Constitutional Thought - Graham Walker (Princeton University Press, 2014)
WHY CAN'T writers interested in constitutional jurisprudence just keep to law and the Constitution? Why do they have to get tangled up in esoteric and unrelated subjects? Such questions mark a common and healthy sentiment. I used to share it, and in part I still do. Unfortunately, it is a sentiment not likely to find satisfaction any time soon. However much we might prefer that constitutional commentators, judges, and scholars stick to narrowly legal matters, they don't—especially recently. It's not that they intend to leave their characteristic concerns behind. What usually gets their commentary started, after all, is the desire to blame or praise some ruling of the Supreme Court. It's just that there is more to thinking about the Constitution and the practices of constitutional government than meets the eye. When a judge steps back from his official duties and tries to become theoretically self-conscious about his enterprise, or when a scholar advances some reading of the First Amendment or some theory of the scope of judicial review in constitutional cases, a kind of thinking occurs that naturally escalates beyond the strictly legal. For serious thinkers who argue for some view of proper judicial demeanor do more than simply assert their view. They inevitably end up justifying it in broader terms of constitutional order; they ponder, for instance, the place of an unelected judiciary within a democracy. Serious thinkers who promote some reading of the First Amendment do not simply proclaim their interpretation self-evident. They end up founding their argument on some larger notions: on some theory of the proper method of constitutional interpretation or even of interpretation generally. As a matter of fact, writers on constitutional issues have in recent years gone much farther than this, pursuing consequential issues seemingly far afield from their immediate concerns. They have been burrowing deeply into moral philosophy, epistemology, theology, aesthetics, and much else in search of grounds to support their positions. I think they have burrowed their way to dead ends, to what I call below "normative impasses." In order to explain my argument, and in order to suggest ways out of these dead ends, I join in the philosophic melee. I delve into ontology, epistemology, theology, morality, and political philosophy. And, perhaps surprisingly, I enlist Augustine's help to do so. But my aim is not to further entangle the Constitution in ultimate questions; my aim is to disentangle it. Though it may not be obvious at first, I turn to Augustine not to take constitutional thought further afield but to bring it back to itself. For an Augustinian way of thinking ultimately offers the sturdiest of reasons why the practices of law and government can—and should—remain concerned with less-than-ultimate matters.